Organic acid synergetic reactive nano-silver ink as well as preparation method and application thereof
A reactive nano-silver ink, which utilizes the synergistic effects of silver citrate, ammonia, and ascorbic acid, solves the conductivity and stability issues of traditional nano-silver inks in high-precision printing and on flexible substrates, achieving the formation and long-term stability of a conductive network at low temperatures.
Patent Information
- Application Number
- CN202511562077.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-29
- Publication Date
- 2025-12-19
AI Technical Summary
Traditional nano-silver particle inks are prone to agglomeration in high-precision inkjet printing, have a narrow viscosity control window, and suffer damage to flexible substrates during high-temperature sintering, making it difficult to form low-resistivity conductive paths.
This reactive nano-silver ink uses silver citrate as the silver source, ammonia as the complexing agent, citric acid as the protective agent, and ascorbic acid as the reducing agent. Nano-silver is generated at low temperature through chemical reduction, forming a stable molecular-level dispersion system, avoiding agglomeration, and forming a continuous conductive network at low temperature.
It achieves good conductivity and film formation after sintering at 140℃, is compatible with flexible substrates, has adjustable viscosity, long shelf life, and is suitable for fine circuit printing.
Smart Images

Figure CN121160143A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of conductive ink technology, specifically to an organic acid-coordinated reactive nano-silver ink, its preparation method, and its application. Background Technology
[0002] As the global electronics and information industry evolves towards miniaturization, flexibility, transparency, and low power consumption, the performance of conductive materials, as the core functional carriers of electronic devices, has become a key bottleneck restricting device integration, reliability, and application expansion. In recent years, the explosive growth of emerging fields such as flexible wearable devices, transparent display panels, Mini / Micro LEDs, flexible photovoltaic modules, and printed electronic circuits (PECs) has placed far greater demands on conductive materials than traditional ones. These demands not only require low resistivity, high mechanical flexibility, and excellent environmental stability, but also compatibility with non-contact high-precision printing processes (such as inkjet printing and flexographic printing) and low-temperature processes to meet the processing needs of new substrates such as flexible polymer substrates (such as PET and PI films) and ultra-thin glass. Against this backdrop, the technological limitations of traditional particulate nano-silver conductive pastes have become increasingly apparent, necessitating breakthroughs in new conductive material systems. Particulate-free nano-silver precursor inks are a key material that has emerged to meet this demand.
[0003] Traditional particulate silver paste uses nano-silver particles (typically 20-100nm in diameter) as the core functional phase, with dispersants stabilizing the particle suspension. However, in high-precision processes such as inkjet printing, this system faces two major problems: First, nanoparticles are prone to agglomeration, directly clogging the printhead and causing printing interruptions or breaks in the conductive path; second, the viscosity and surface tension control window of the particulate dispersion system is narrow—to avoid particle sedimentation, a high viscosity must be maintained, but high viscosity leads to uneven droplet spreading, making it difficult to form fine circuits with linewidths <50μm, while reducing viscosity, although improving printability, exacerbates particle sedimentation, resulting in a shortened ink shelf life; on the other hand, traditional silver paste requires high-temperature sintering to achieve fusion bonding between particles, but the core substrates of emerging flexible electronic devices (such as PET film with a temperature resistance of <120℃, PI...)... Thin films with a temperature resistance of <200℃ cannot withstand this high-temperature process. If the sintering temperature is forcibly reduced (e.g., below 150℃), only physical contact can be formed between the particles, resulting in a large number of gaps in the conductive path, which leads to a significant increase in resistance and poor mechanical stability. After repeated bending, the resistance increases significantly. Even in the field of rigid substrates, high-temperature sintering has its drawbacks: for example, in ultra-thin glass-based transparent display panels, sintering temperatures above 240℃ can cause thermal deformation of the glass, affecting the flatness of the panel; and in the manufacturing of multilayer PCBs, high temperatures can damage the adhesive layer between substrates, leading to interlayer delamination.
[0004] It should be noted that the background information disclosed above is intended only to enhance the understanding of the overall background of the present invention and to help understand the context in which the inventors developed their inventive concept, and should not be construed as an admission or in any way implying that the information constitutes prior art known to those skilled in the art.
[0005] A search revealed Chinese patent document CN104479463A (hereinafter referred to as D1) which discloses a transparent, conductive, particle-free silver-based ink containing silver oxalate. This ink is composed of silver oxalate, an amine solvent, a reducing agent, and a solvent, with a mass percentage of (4.22-67.56%):(5-95.78%):(0-50%):(0-65%). The preparation method involves mixing the amine solvent, reducing agent, and solvent, then mixing them with silver oxalate; stirring at -5 to 10°C for 0.5 to 4 hours until dissolved; and finally filtering to obtain the conductive ink. The viscosity range of the obtained ink is 1 mPa·s to 1000 mPa·s. This method is simple and readily available. The ink can be formed on a substrate by printing or coating, with low curing temperature, short curing time, high stability, good conductivity, and good toughness and tensile strength, which is beneficial for bending.
[0006] Chinese patent document CN120089432A (hereinafter referred to as D2) discloses an organic silver paste comprising the following components by weight: 6-45 parts inorganic silver powder; 5-30 parts organic silver; 5-20 parts glass powder; 10-30 parts organic carrier; 8-32 parts organic acid; and 1-5 parts additives. The organic carrier includes an organic binder and a solvent, and the mass ratio of the organic binder, organic silver, and organic acid is 1:(1-4):(1-6). The organic silver is at least one of saturated fatty acid silver, silver citrate, silver oxalate, and silver benzoate, and the particle size of the organic silver is 1-10 μm. The organic binder contains 5-10% by mass of groups capable of forming hydrogen bonds. The inorganic silver powder includes inorganic silver powder A and inorganic silver powder B, and the mass ratio of inorganic silver powder A, inorganic silver powder B, and organic silver is 1:(0.5-4):(0.5-4). This organic silver paste exhibits excellent conductivity and printability.
[0007] Analysis revealed that the core silver source in D1 is silver oxalate (Ag₂C₂O₄). The citric acid used in D1 acts as a reducing agent, participating in the silver ion reduction process, thus requiring a significantly larger amount of citric acid, necessitating its direct use. Furthermore, the role of citric acid as a reducing agent is related to the order in which components are added during the preparation of D1. Therefore, even if D1 combines with D2, it does not affect the innovation of this invention.
[0008] Thus, this invention application was filed. Summary of the Invention
[0009] Therefore, this invention has a different inventive concept from the prior art, and through independent research, proposes an organic acid-synergistic reactive nano-silver ink, its preparation method and application. This reactive nano-silver ink exhibits good conductivity and film-forming effect after sintering at 140℃.
[0010] The technical solution adopted is as follows:
[0011] The present invention discloses a method for preparing an organic acid-co-synergistic reactive nano-silver ink, comprising the following steps:
[0012] S1. Weigh silver citrate into a container, add ammonia, sonicate, let stand at room temperature, and then filter to obtain the intermediate mixture;
[0013] S2. Add a citric acid aqueous solution with a concentration of 3wt%-7wt% to the intermediate mixture, then add ascorbic acid, sonicate, let stand, take the supernatant and filter, let the obtained filtrate stand again and filter a second time to obtain reactive nano silver ink.
[0014] Furthermore, the mass ratio of silver citrate, ammonia, citric acid aqueous solution and ascorbic acid is 1:(1-2):(0.6-0.9):(0.1-0.3).
[0015] Furthermore, the mass ratio of silver citrate, ammonia, citric acid aqueous solution and ascorbic acid is 1:1.2:0.8:0.2, respectively.
[0016] Furthermore, in step S1, the concentration of the ammonia water is 25 wt%.
[0017] Furthermore, in step S2, the concentration of the citric acid aqueous solution is 5%.
[0018] Further, in step S1, after sonication for 15 minutes and standing at room temperature for 12 hours, the intermediate mixture is obtained by filtration.
[0019] Further, in step S2, after sonication for 15 minutes, the supernatant is collected and filtered after standing for 24 hours. The resulting filtrate is then allowed to stand for another 24 hours and filtered a second time to obtain reactive nano-silver ink.
[0020] The present invention provides an organic acid-synergistic reactive nano-silver ink, which is prepared by the preparation method described above.
[0021] The application of the organic acid-synergistic reactive nano-silver ink described in this invention in the preparation of conductive cotton yarn.
[0022] Furthermore, the preparation method of the conductive cotton yarn includes the following steps: immersing the substrate cotton yarn in the reactive nano-silver ink, and then sintering it at a constant temperature of 160°C for 30 minutes to obtain the final product.
[0023] In the above technical solutions,
[0024] Reactive nano-silver ink is a molecular-level dispersion system with silver-based compounds or silver complexes (such as silver ammonia complexes, silver-thiourea complexes, and silver carboxylate salts) as the core functional phase. Essentially, it is a precursor solution that can be converted into metallic silver. Through chemical reduction, thermal reduction, or photoreduction, nano-silver can be generated in situ at low temperatures, forming conductive pathways. The core functional phase of the reactive ink is uniformly dispersed in the liquid phase as a complex, allowing for flexible control of the ink viscosity. This makes it suitable for inkjet printing with nozzles smaller than 10 μm, forming fine conductive pathways to meet the needs of micro- and nano-electronics. Furthermore, the molecular-level dispersion system exhibits extremely high stability, with a shelf life of up to six months when stored at low temperature and in the dark. The precursor ink has a low activation energy, allowing it to be converted into metallic silver without high-temperature sintering.
[0025] This invention designs a reactive nano-silver ink using silver citrate as the silver source, ammonia as the complexing agent, citric acid (CA) as the protective agent, and ascorbic acid as the reducing agent. Based on each component, the silver ions and citrate ions in the silver citrate molecule are bound by coordinate bonds, and can slowly dissociate into Ag in the solvent. + This avoids the aggregation problem of traditional silver nanoparticles, and silver citrate has excellent organic compatibility, forming a stable molecular-level dispersion system. Ammonia water can react with Ag. + [Ag(NH3)2] is formed. + Citric acid, on the other hand, undergoes secondary coordination with silver ammonia complex via hydroxyl groups to form "Ag + The ternary complex "-NH3-CA" improves the controllability and stability of the entire preparation process. The hydroxyl and carboxyl groups in citric acid molecules can interact with the solvent through hydrogen bonding, forming steric hindrance in solution and preventing the aggregation of silver nanoparticles during reduction. The reducing power of ascorbic acid is significantly affected by pH; under weakly alkaline conditions, the enediol structure of ascorbic acid is easily oxidized to dehydroascorbic acid, while simultaneously reducing Ag... + Restored to Ag 0 Compared to strong reducing agents, ascorbic acid has a controllable reduction rate, which can avoid the aggregation caused by the rapid growth of silver nanocrystals, and its oxidation products are non-toxic, which is beneficial to the environment.
[0026] Based on the synergistic mechanism of organic acids, citric acid "anchors" Ag through coordination. + This restricts the diffusion rate, creating a controllable ion transport environment for the reaction system. The addition of a small amount of ascorbic acid selectively reduces the "anchored" Ag. + This provides the ink with "seeds" of small-sized nanoparticles, which have the following advantages:
[0027] 1. It can serve as a heterogeneous nucleation site for silver ions (Ag). +The reduction of α provides a thermodynamic advantage. According to classical nucleation theory, the critical free energy for heterogeneous nucleation is much lower than that for homogeneous nucleation—the surface atoms of small-sized nanoparticles have high mobility and can adsorb surrounding Ag. + And accelerate its reduction to Ag by accepting electrons. 0 , making Ag 0 It is easier for it to grow on the particle surface rather than reform new nuclei, thereby reducing the activation energy of the reduction process.
[0028] 2. For systems centered on silver citrate and silver ammonia complexes, the surface of small-sized silver nanoparticles can serve as catalytic active sites, accelerating the thermal decomposition of precursors. The decomposition of silver citrate used in this invention requires the breaking of Ag-O bonds, and the unsaturated bonds on the surface of the silver nanoparticles can adsorb citrate ions, lowering the activation energy for bond breaking. Furthermore, the small-sized silver nanoparticles can catalyze the reaction of organic molecules with oxygen at lower temperatures, generating CO2 and H2O, reducing the damage to flexible substrates caused by traditional high-temperature sintering.
[0029] 3. The crystal structure of small-sized nanoparticles can serve as a lattice-matching template, enabling newly generated Ag to... 0 Directional growth forms a continuous conductive network. This directional growth reduces the "disorderly agglomeration" phenomenon in traditional homogeneous nucleation, and the small particles gradually melt and diffuse towards the large particles with low surface energy during sintering, making the silver grain size distribution more uniform and avoiding excessively large pores or defects.
[0030] Compared to D1 (CN104479463A), where the core silver source is silver oxalate (Ag2C2O4), this invention uses silver citrate (C6H5Ag3O7). The silver source used in this invention has superior water solubility and thermal stability, making it more suitable for liquid-phase reaction systems to ensure reaction stability and controllability. Furthermore, in D1, citric acid acts as a reducing agent, participating in the silver ion reduction process, while in this invention, citric acid functions as a protective agent, achieving complex ion stabilization and regulation through the formation of a mixed coordination structure with silver ions. The mechanisms of action of the two core components are completely different. In the preparation method of D1, the amine solvent, reducing agent, and solvent are first mixed before being mixed with silver oxalate. This makes citric acid act as a reducing agent in the silver ion reduction process with silver oxalate, resulting in a significantly larger amount of citric acid used directly. Moreover, the mechanism of action of D1 as a reducing agent is completely different from the mechanism of action of this invention as a protective agent. This invention uses a citric acid aqueous solution with a concentration of 3wt%-7wt%. Further diluting the citric acid with water to a concentration of 3wt%-7wt% is sufficient to achieve its function as a protective agent. Ultimately, this results in the reactive nano-silver ink of this invention exhibiting excellent conductivity and film-forming effect after sintering at 140℃. This is not achieved in prior art document 1.
[0031] Although patent D2 (CN120089432A) uses silver citrate as the silver source, the final product of that patent is a resin-based silver paste, while the target product of this invention is a reactive nano-silver ink. The two differ fundamentally in product form, system composition, and application scenarios, making their technical solutions incomparable. Even if D2 is used as a reference document, and even if it is combined with D1, this invention cannot be obtained. This invention differs significantly from the technical routes of D1 and D2 mentioned above, possessing independent innovation.
[0032] In summary, the beneficial effects of this invention are as follows:
[0033] The reactive nano-silver ink prepared by this invention achieves complex ion stabilization and regulation by forming a mixed coordination structure between citric acid and silver ions, and synergistically complexes with ammonia (in step S1, ammonia first reacts with Ag...). + [Ag(NH3)2] is formed. + In step S2, citric acid undergoes secondary coordination with silver ammonia complex via hydroxyl groups to form "Ag + (-NH3-CA” ternary complex), and then ascorbic acid was added. Combined with the controllable reduction of ascorbic acid, a stable nano-silver precursor system was constructed. Furthermore, the addition of low concentration of ascorbic acid to generate a small amount of nano-silver seeds has a significant catalytic and promoting effect on subsequent sintering, so that the ink has good conductivity and film-forming effect after sintering at 140℃. Attached Figure Description
[0034] Figure 1 The images show the macroscopic morphology and visible-ultraviolet (UV) spectra of ink samples 1-3 in Experiment 1. (a)-(c) show the macroscopic morphology of ink samples 1-3, (d)-(f) show the macroscopic morphology of ink samples 1-3 after 60 days of storage, and (h) shows the UV spectra of ink samples 1-3.
[0035] Figure 2 The XRD patterns are of ink samples 1-3 in Experiment 2.
[0036] Figure 3 The images show a portion of the experimental results for sample ink in Experiment 3. (a) Microstructure of the precursor of sample 3; (b) HRTEM (High Resolution Transmission Electron Microscopy) image; (c) Microstructure after sintering at 180℃ for 5 min.
[0037] Figure 4 The following are some experimental results of the ink sample No. 3 in Experiment 3. Among them, (a) microstructure after sintering at 180℃ for 30 min; (b) HRTEM image; (c) EDS (Energy Dispersive X-ray Difference) image; (d)-(g) Mapping (elemental distribution analysis) images.
[0038] Figure 5 The resistivity curves of ink samples 1-3 in Experiment 4 are shown as a function of temperature.
[0039] Figure 6 The figures show the experimental results of samples 3 and 1 in Experiment 5. (a)-(d) are SEM images of sample 3 at different heating temperatures: (a) 140℃ (b) 160℃ (c) 180℃ (d) 200℃; (e)-(h) are SEM images of sample 3 at different heating times: (e) 1 min (f) 5 min (g) 10 min (h) 20 min; (i) is the SEM image of sample 1 after sintering at 180℃ for 20 min.
[0040] Figure 7 The diagram shows the contact angle of ink sample 3 in Experiment 6.
[0041] Figure 8 The graph shows the resistance change of ink sample 3 in Experiment 7. (a) shows the resistance change after different number of bends; (b) shows the resistance change after different number of immersions.
[0042] Figure 9 The images show the experimental results of ink sample 3 in Experiment 8. Among them, (a) is a diagram of the simplified direct-write test apparatus; (b) is a morphology diagram before sintering after different direct-write cycles; (c) is a morphology diagram after sintering after different direct-write cycles; (d) is a low-magnification microscopic morphology diagram after different direct-write cycles; (e) is a macroscopic morphology diagram after 14 direct-write cycles; and (f) is a microscopic morphology diagram after 14 direct-write cycles. Detailed Implementation
[0043] The present invention will be described in detail below through specific embodiments. However, the uses and purposes of these exemplary embodiments are only for illustrating the present invention and do not constitute any limitation on the actual protection scope of the present invention, nor are they intended to limit the protection scope of the present invention to this.
[0044] Comparative Example 1
[0045] The preparation method of the ink in this comparative example includes the following steps:
[0046] (1) Weigh 0.5g of silver citrate into a glass container and add 0.6g of ammonia (25wt%). Sonicate for 15min, let stand at room temperature for 12h, and then filter to obtain sample No. 1.
[0047] Comparative Example 2
[0048] The preparation method of the ink in this comparative example includes the following steps:
[0049] (1) Weigh 0.5g of silver citrate into a glass container and add 0.6g of ammonia (25wt%). Sonicate for 15min, let stand at room temperature for 12h, and then filter to obtain sample No. 1.
[0050] (2) Add 0.05g of ascorbic acid to sample 1, sonicate for 15min, remove and place at room temperature in the dark for 36h, then take the supernatant and filter to obtain sample 2.
[0051] Example 1
[0052] The preparation method of the reactive nano-silver ink in this embodiment includes the following steps:
[0053] (1) Weigh 0.5g of silver citrate into a glass container, add 0.6g of concentrated ammonia, sonicate for 15min, let stand at room temperature for 12h, and then filter to obtain sample No. 1.
[0054] (2) Add 0.4g of citric acid aqueous solution (5wt%) to sample 1, then add 0.1g of ascorbic acid, sonicate for 15min, let stand for 24h, take the supernatant and filter, let the obtained filtrate stand for another 24h and filter a second time to obtain sample 3.
[0055] Experimental test:
[0056] Experiment 1
[0057] The three inks corresponding to samples No. 1, No. 2, and No. 3 were subjected to visible and ultraviolet light tests at 0 days and 60 days, respectively, and their macroscopic morphology was observed. The results are as follows: Figure 1 As shown, where Figure 1 In the image, (a), (b), and (c) show the macroscopic morphology of the freshly prepared ink, and it can be seen that inks 1-3 are transparent and clear. Figure 1 In the figures, (d), (e), and (f) show the macroscopic morphology of the ink after 60 days. It can be observed that ink No. 1 and No. 2 have become slightly cloudy, while ink No. 3 remains clear. Figure 1 In the figure, (h) represents the visible ultraviolet spectrum. At day 0, the absorption peak intensities of the three inks were all weak, indicating that almost no silver particles were precipitated in the three inks. After 60 days, inks 1 and 2 showed obvious absorption peaks at a wavelength of about 400 nm, while ink 3 had almost no absorption peak, indicating that ink 3 was more stable at room temperature and was less likely to precipitate silver particles.
[0058] Experiment 2
[0059] The prepared ink was cured at 180℃ for 30 minutes and then subjected to XRD testing. The results are as follows: Figure 2The XRD patterns of ink samples 1-3 are shown. The silver diffraction peak intensity in sample 1 is relatively weak, indicating that the degree of silver crystallization is low. The diffraction peak intensity of sample 2 is significantly enhanced after the addition of ascorbic acid. Sample 3 shows strong diffraction peaks at 38°, 44°, 64°, 77° and 82°, corresponding to the silver crystal planes (111), (200), (220), (311) and (222), which match PDF#87 – 0597 (fcc type), indicating that the reduced silver particles have good crystallinity.
[0060] Experiment 3
[0061] TEM (transmission electron microscopy) was performed on sample No. 3, and the results are as follows: Figure 3 and Figure 4 As shown, where Figure 3 In (a), the precursor ink (before sintering) is uniformly distributed with nano-silver particles as seeds. Figure 3 (b) is an HRTEM image of the silver nanoparticle seeds, which shows obvious lattice fringes with a lattice spacing of 0.2 nm, which is highly consistent with the (200) interplanar spacing (approximately 0.204 nm) of the face-centered cubic (fcc) structure of silver nanoparticles. Figure 3 Figure 4(c) shows the morphology of the nanoparticles after sintering at 180°C for 5 min. Silver ions undergo heterogeneous nucleation on the surface of the nanocrystal seeds, resulting in the rapid formation of a large number of nanoparticles during sintering. Figure 4(a) shows the morphology after sintering at 180°C for 30 min, where it is evident that the particles have melted. Figure 4(b) shows that as the heating time increases, the particles in the system gradually melt. This melting process provides an effective channel for material transport and eliminates interfacial defects between particles, driving the crystallization process to deepen and crystal growth, thus further improving the crystallinity of the particles. Further analysis based on the characterization results in Figures 4(c)-(g) indicates that the particles formed after melting are pure silver nanoparticles, and XRD diffraction patterns show that the silver particles were not oxidized during the sintering process.
[0062] Experiment 4
[0063] The three inks, corresponding to No. 1, No. 2, and No. 3, were uniformly coated onto a glass substrate. The resistance changes were measured under different heating conditions, and the results are as follows: Figure 5 As shown, the resistivity gradually decreases with increasing heating temperature, reaching a minimum of 10 when the temperature reaches 200℃. -5Comparing samples 1, 2, and 3 (Ω·cm), it can be seen that sample 3, after adding citric acid aqueous solution first and then ascorbic acid, has a lower resistivity than samples 1 and 2. This confirms that the silver nanoparticle seeds generated in sample 3 play a catalytic and promoting role in the sintering process, lowering the reduction temperature of the entire system. This demonstrates that after constructing a stable silver nanoparticle precursor system, adding a small amount of low-concentration ascorbic acid to generate a small amount of silver nanoparticle seeds has a significant catalytic and promoting effect on subsequent sintering.
[0064] Experiment 5
[0065] See Figure 6 The image shown is a SEM image of sample ink #3 after sintering on a PI film. Figure 6 Figures (a)-(d) show the microstructure of sample 3 at different heating temperatures, all with a heating time of 15 min. It is clearly observed that at low temperature (140 °C), a large number of silver nanoparticles are reduced. However, at this time, the particles only form a conductive network through simple physical contact, resulting in a loose network structure with high porosity. As the heating temperature increases, the reduced particles sinter together, forming sintering necks, further reducing the porosity of the conductive network, decreasing the contact resistance between particles, and improving the overall conductivity of the film. Figures (e)-(h) in Figure 6 show the microstructure of silver nanoparticles at different heating times. The changes in the images clearly show the transformation process of the silver nanoparticles from initial growth to complete melting. Figure 6(i) shows the microstructure of sample 1 after sintering at 180 °C. Comparing it with Figure 6(h), it can be seen that sample 1 has more pores in its microstructure, further confirming that the addition of ascorbic acid can effectively optimize the film formation effect during the sintering process.
[0066] Experiment 6
[0067] Contact angle tests were conducted by coating ink No. 3 onto a PI film (low surface energy) and a silicon substrate (high surface energy), respectively. The results are as follows: Figure 7 As shown, the PI film exhibits good wettability on both substrates, but the contact angle on the PI film is always larger than that on the glass substrate. This is because the high surface energy glass contains polar hydroxyl groups, which form a strong interaction with the polar components in the ink (such as ascorbic acid), promoting its spread and resulting in a small contact angle. The low surface energy PI film contains non-polar aromatic rings, which have a weak interaction with the ink, resulting in greater spread resistance and a higher contact angle.
[0068] Experiment 7
[0069] To meet the application requirements of flexible electronic materials, conductive cotton yarn was prepared using an impregnation-sintering process: the substrate cotton yarn was immersed in sample No. 3, and after sintering at 160℃ for 30 min, the change in resistance under different bending times was tested. The effect of the number of immersion cycles on the resistance was also investigated. The results are as follows: Figure 8 As shown in Figure 8(a), the resistance of the conductive cotton yarn generally increases with the number of bends. After 100 cycles of bending, the resistance increase is only 50%, indicating that it has good flexible conductive stability and can be adapted to the dynamic application scenarios of flexible electronics. However, the resistance decreases in stages when the number of bends reaches 60. This is because the repeated bending causes the bending area of the cotton yarn to continuously shrink and deform, which reduces the contact gap of the silver particles on the surface and increases the density, thus optimizing the continuity of the conductive path. Figure 8(b) shows that the resistance of the conductive cotton yarn decreases significantly with the number of sample immersions. After 5 immersions, the resistance basically stabilizes. The reason is that the more immersions, the higher the concentration of silver ions adsorbed by the cotton yarn, and the greater the density of silver particles generated by reduction during subsequent sintering. The conductive network formed on the surface of the cotton yarn and between the fibers is more complete and continuous. After 5 immersions, the silver particles can build a conductive network that meets the requirements of low resistance. The effect of further increasing the number of immersions on the conductive network is weakened, so the resistance no longer changes significantly.
[0070] Experiment 8
[0071] To verify the application potential of conductive ink in direct-write molding, this study filled the ink into a 0.5 mm diameter syringe for direct-write testing, focusing on the evolution of the microstructure of the film after sintering under different direct-write cycles. The experimental results are as follows: Figure 9 As shown, Figure 9 Figure 9(a) shows the assembly diagram of the direct-write test. Figure 9(b) and (c) show the macroscopic morphology of the film before and after heating, respectively, which intuitively presents the influence of the sintering process on the appearance of the film. Figure 9(d) shows the optical micrographs of the film with different direct-write times. As the number of direct-write times increases, the packing density of conductive particles in the film gradually increases, the conductive network gradually becomes denser, and the continuity of the conductive path is significantly enhanced, which provides structural support for the improvement of the conductive performance of the film. Figure 9(e) shows the macroscopic morphology of the film with 14 direct write times, and Figure 9(f) shows the microscopic morphology of the film with 14 direct write times. It can be clearly observed that the film has completed the metallization process after sintering and formed a continuous structure with conductive function.
[0072] In summary, this conductive ink exhibits excellent morphology controllability and structural stability in direct-write molding tests, making it suitable for applications in direct-write fabrication processes and flexible electronics.
[0073] The detailed descriptions listed above are merely specific illustrations of feasible embodiments of the present invention and are not intended to limit the scope of protection of the present invention. All equivalent embodiments or modifications made without departing from the spirit of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing an organic acid-coordinated reactive nano-silver ink, characterized in that, Includes the following steps: S1. Weigh silver citrate into a container, add ammonia, sonicate, let stand at room temperature, and then filter to obtain the intermediate mixture; S2. Add a citric acid aqueous solution with a concentration of 3wt%-7wt% to the intermediate mixture, then add ascorbic acid, sonicate, let stand, take the supernatant and filter, let the obtained filtrate stand again and filter a second time to obtain reactive nano silver ink.
2. The method for preparing organic acid-synergistic reactive nano-silver ink according to claim 1, characterized in that, The mass ratio of silver citrate, ammonia, citric acid aqueous solution and ascorbic acid is 1:(1-2):(0.6-0.9):(0.1-0.3).
3. The method for preparing organic acid-synergistic reactive nano-silver ink according to claim 2, characterized in that, The mass ratio of silver citrate, ammonia, citric acid aqueous solution and ascorbic acid is 1:1.2:0.8:0.
2.
4. The method for preparing organic acid-synergistic reactive nano-silver ink according to claim 1, characterized in that, In step S1, the concentration of the ammonia water is 25 wt%.
5. The method for preparing organic acid-synergistic reactive nano-silver ink according to claim 1, characterized in that, In step S2, the concentration of the citric acid aqueous solution is 5%.
6. The method for preparing organic acid-synergistic reactive nano-silver ink according to claim 1, characterized in that, In step S1, the mixture is sonicated for 15 minutes, allowed to stand at room temperature for 12 hours, and then filtered to obtain the intermediate mixture.
7. The method for preparing organic acid-synergistic reactive nano-silver ink according to claim 1, characterized in that, In step S2, after sonication for 15 minutes, the supernatant was collected and filtered after standing for 24 hours. The resulting filtrate was then allowed to stand for another 24 hours and filtered a second time to obtain reactive nano-silver ink.
8. An organic acid-co-synergistic reactive nano-silver ink, characterized in that, It is prepared by the preparation method described in any one of claims 1-7.
9. The application of the organic acid-synergistic reactive nano-silver ink of claim 8 in the preparation of conductive cotton yarn.
10. The application according to claim 9, characterized in that, The preparation method of the conductive cotton yarn includes the following steps: immersing the substrate cotton yarn in the reactive nano-silver ink, and then sintering it at a constant temperature of 160℃ for 30 minutes to obtain the final product.
Citation Information
Patent Citations
Transparent conductive particle-free silver-based ink with silver oxalate and preparation method thereof
CN104479463A
Organic silver paste and preparation method and application thereof
CN120089432A